DAMPAK FENOMENA “NO VIRAL, NO JUSTICE” TERHADAP PENEGAKAN HUKUM KASUS KDRT DI INDONESIA - Nur, Hilman; Lananda, Ardelia; Simbolon, Cindy Claudia; Rahmah, Mila Arastasya; Baidhowi, Nayla Ratu; Januwati, Pusfa; Dika, Muhammad Gilar; Tri Cahya, Muhammad Agung (LPPM Universitas Doktor Husni Ingratubun Papua, 2025)
The phenomenon of “No Viral, No Justice” has become a highlight in handling cases of Domestic Violence (DV) in Indonesia. This phenomenon reflects the public perception that justice is often only achieved if cases of Domestic Violence (DV) receive widespread attention on social media. The purpose of this study is to analyze in more depth the law enforcement system for domestic violence crimes in Indonesia based on applicable laws and regulations, identify the factors causing the emergence of the phenomenon of “No Viral, No Justice” in law enforcement of domestic violence in Indonesia and examine the impact of the phenomenon of “No Viral, No Justice” on the effectiveness of law enforcement officers in handling domestic violence crimes in Indonesia. The method used in this study is the normative legal research method. This research method is carried out by examining problems and processing data obtained from legal regulations in accordance with existing regulations and rules or norms as the basis for research. The results of the study indicate that the phenomenon of “No Viral, No Justice” on social media can accelerate the law enforcement process and increase public pressure on law enforcement officers to act. However, this phenomenon can also pose risks, such as trials by the media, violations of victim privacy, and potential disinformation. In addition, dependence on virality can divert attention from systematic and sustainable efforts to address Domestic Violence (DV), so efforts are needed to strengthen effective and reliable mechanisms for protecting victims of Domestic Violence (DV).